Cutaneous adverse effects of BRAF inhibitors in metastatic malignant melanoma, a prospective study in 20 patients. (24th March 2014) - Vanneste, L.; Wolter, P.; Van den Oord, J.J.; Stas, M.; Garmyn, M.
Abstract Background BRAF inhibitors frequently cause significant cutaneous adverse reactions. Objective To study the timing, prevalence and response to treatment of skin lesions in patients receiving V‐raf murine sarcoma viral oncogene homolog B1 (BRAF) inhibitors. Methods We prospectively studied the cutaneous side‐effects of patients with a BRAF mutant (V600E, V600K, V600R) metastatic malignant melanoma treated with a BRAF inhibitor. We systematically registered prevalence, timing of onset and response to treatment. Results Twenty patients were treated for 2–52 weeks with a BRAF inhibitor. Eleven patients on vemurafenib (58%) developed cutaneous side‐effects and 10 patients (42%) had more than one cutaneous adverse event. Verrucous papillomas were observed in eight patients (42%), after 1–12 weeks. We diagnosed four keratoacanthomas in two patients (11%) after 6–10 weeks and two squamous cell carcinomas in two patients (11%) after 10–16 weeks. Seven patients (37%) developed a hyperkeratotic, folliculocentric eruption after 2–8 weeks, resolving quickly under topical steroids. Four patients (21%) presented a facial erythema, two patients (11%) a seborrhoeic dermatitis‐like eczema on the scalp. Three patients (16%) developed cystic lesions after 2–11 weeks. Three patients (16%) presented a hand–foot skin reaction after 4–6 weeks, which was successfully treated with topical steroids and keratolytics. Hyperkeratosis of the nipples was seen in one patient (5%). We observed phototoxic reactions after UV exposure in five patients (26%) and alopecia in two patients (11%) after 8–10 weeks. One patient on dabrafenib developed curly hairs (24 weeks), keratotic papules (1 and 36 weeks), a keratoacanthoma (4 weeks) and a hand–foot skin reaction (31 weeks). Conclusion Multiple cutaneous toxicities were observed in patients under BRAF inhibitors, mostly well controlled with adequate treatment. We recommend a multidisciplinary approach with regular assessments of the skin by a dermatologist. This allows early identification and adequate treatment to avoid premature discontinuation of a life‐prolonging therapy.